Clinical significance of serum glucose to lymphocyte ratio as a prognostic marker in peritoneal dialysis patients - Jiexin Chen; Ruiying Tang; Xiaojiang Zhan; Jihong Deng; Yanxia Zhang; Haibo Long; Fenfen Peng; Na Tian; Yueqiang Wen; Xiaoyang Wang; Xiaoran Feng; Ning Su; et al. (Renal Failure)
Background The glucose-to-lymphocyte ratio (GLR), a glucose metabolism and systemic inflammatory response parameter, is associated with an adverse prognosis for various diseases. However, the association between serum GLR and prognosis in patients undergoing peritoneal dialysis (PD) is poorly understood.Methods In this multi-center cohort study, 3236 PD patients were consecutively enrolled between 1 January 2009 and 31 December 2018. Patients were divided into four groups according to the quartiles of baseline GLR levels (Q1: GLR ≤ 2.91, Q2:2.91 < GLR ≤ 3.91, Q3:3.91 < GLR < 5.59 and Q4: GLR ≥ 5.59). The primary endpoint was all-cause and cardiovascular disease (CVD) related mortality. The correlation between GLR and mortality was examined using Kaplan–Meier and multivariable Cox proportional analyses.Results During the follow-up period of 45.93 ± 29.01 months, 25.53% (826/3236) patients died, of whom 31% (254/826) were in Q4 (GLR ≥ 5.59). Multivariable analysis revealed that GLR was significantly associated with all-cause mortality (adjusted HR 1.02; CI 1.00 ∼ 1.04, p = .019) and CVD mortality (adjusted HR 1.02; CI 1.00 ∼ 1.04, p = .04). Compared with the Q1 (GLR ≤ 2.91), placement in Q4 was associated with an increased risk of all-cause mortality (adjusted HR: 1.26, 95% CI: 1.02 ∼ 1.56, p = .03) and CVD mortality (adjusted HR 1.76; CI 1.31 ∼ 2.38, p < .001). A nonlinear relationship was found between GLR and all-cause or CVD mortality in patients undergoing PD (p = .032).Conclusion A higher serum GLR level is an independent prognostic factor for all-cause and CVD mortality in patients undergoing PD, suggesting that more attention should be paid to GLR.